Design of Robust-Performance Compensators for Control Speed of A Double-Sided Linear Induction Motor With Ladder-Secondary - Rusli, Mochammad; Choiron, Moch Agus; Muslim, Muhammad Aziz; Yuwono, Rudy; Kusmaryanto, Sigit; Wardana, I.N.G. (International Journal of Engineering and Technology, 2018)
This paper proposes an inovative linear speed robust-controller design. The uncertainty model is developed in combination between multiplicative and addotive structures. The robust controller is referred on feedforward and feedback strategies.  For speed controller is employed a error quadratic approximation  for calculation of  robust digital algorithm using the interpolation metjod.  A discontinue-Secondary Double-Sided Linear Motor (DSLIM) as drive was modelled using magnetic path approximation. Especially,  the error quadratc method will be employed in finding  of unstructured discrete  controller for a double-sided  linear induction motors with ladder-secondary  to obtain position tracking precisely. A decouple process is aimed to linearization of nonlinear mathematic model of DSLIM, so that it can make a simplification of controller design algorithm. Additionally, the inherent characteristic of linear induction motor:  longitudinal end effect is also considered and is taken in account for arranging  the controller design algorithm. Also, the digital r simulations are built for demonstrating the performance of closed loop speed control with various parameters of DSLIM (robustness). The vector control algorithm will be for achieving the controller in stand still condition.